Hurting the Qur'an - Suggestions Concerning the Psychological Infrastructure of Desecration - Svensson, Jonas (Temenos, 2017)
Recent years have witnessed several examples of desecrations of copies of the Qur'an as a display of non-Muslim hostility against Muslims. The present article attempts to answer a fundamental question relating to this phenomenon: how do desecrators know what acts directed at the Qur'an are likely to offend Muslims? The suggestion put forward is that desecration is an act that can be understood across cultural and religious boundaries because it is based on shared, intuitive knowledge of what the sacredness of an object entails. This knowledge, in turn, rests upon certain mental operations involved in the process of sacralisation: i.e. when things are set apart and forbidden'. When the mental processes of psychological essentialism and conceptual blending are combined, it results in a partial personification of the sacred object, providing inferences concerning which acts count as desecrations, i.e. acts that, had they been directed at a person, would cause harm, whether physical or psychological.